2015
DOI: 10.1371/journal.pone.0140402
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of Dietary n-6/n-3 Polyunsaturated Fatty Acids Independently Related to Muscle Mass Decline in Hemodialysis Patients

Abstract: Backgroundn-3 polyunsaturated fatty acids (PUFAs) might be useful nutritional strategy for treating patients with sarcopenia. We evaluated the effect of the intake of dietary n-3 PUFAs on the skeletal muscle mass (SMM), appendicular skeletal muscle mass (ASM), and its determinants in patients receiving standard hemodialysis (HD) treatment for the management of end stage renal disease.MethodsIn this cross-sectional study, data of 111 HD patients were analyzed. Anthropometric and bioelectrical impedance measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Unfortunately, this ratio has been changed to 1:20 over the past 150 years due to the less n-3 and excess n-6 PUFAs in our modern diets78. Regarding the critical role for n-3 PUFAs in regulating organ development and function, the deficiency of n-3 PUFAs and the low n-3/n-6 ratio are detrimental for the healthy in human beings910111213.…”
mentioning
confidence: 99%
“…Unfortunately, this ratio has been changed to 1:20 over the past 150 years due to the less n-3 and excess n-6 PUFAs in our modern diets78. Regarding the critical role for n-3 PUFAs in regulating organ development and function, the deficiency of n-3 PUFAs and the low n-3/n-6 ratio are detrimental for the healthy in human beings910111213.…”
mentioning
confidence: 99%
“…The information regarding age, gender, hemodialysis vintage, comorbidities calculated using the Charlson comorbidity index [ 33 ], history of hypertension, cardiovascular diseases, and type 2 diabetes mellitus (T2DM), body mass index, BMI (kg/m 2 ), pre-dialysis systolic (SBP) and diastolic (DBP) blood pressure were also assessed using medical records. The waist circumference (WC), body fat mass (FM) were assessed using the bio-electrical impedance analysis device (InBody S10, Biospace, Seoul, Korea), the detailed procedure was described elsewhere [ 34 ]. Elevated body fat mass was defined as FM ≥ 25% for men, FM ≥ 30% for women, respectively [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…We demonstrated that reduced dietary omega-3 fatty acids intake was associated with the presence of sarcopenia in elderly patients with type 2 diabetes. Although several studies showed that some fatty acids such as omega-3 fatty acids or maslinic acid intake was associated with muscle strength and muscle mass in healthy elderly people, (8,9,(12)(13)(14)(15)31) to our knowledge, the present study is the first survey to identify the association between omega-3 fatty acids intake and sarcopenia in elderly patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 77%
“…(10,11) Omega-3 fatty acids supple-mentation increased muscle mass and strength in elderly healthy individuals. (12,13) While several previous reports demonstrated that dietary omega-3 fatty acids intake was associated with muscle strength, (10,14,15) few studies reported the association between dietary omega-3 fatty acids intake and muscle mass. (9) Thus, we aimed to investigate the association between dietary omega-3 fatty acids intake and sarcopenia diagnosed by both muscle strength and mass in elderly patients with type 2 diabetes.…”
mentioning
confidence: 99%